End, End, End and For Issa (AmeriQuests, 2015)
Video Synopsis: End, End, End is a meditation on the fragmentary nature of thoughts, memories, and emotions. Combining found recordings of a man marking the beginning and end of analog audio tapes with a collage of images of the natural world, this experimental short weaves in and out of the past and present, stopping along the way to reflect on death, love, and the appropriate way to make a cup of coffee. This work suggests at once a desperate desire for narrative understanding and the impossibility of ever achieving it.Video SYNOPSIS: For Issa is a short work composed as a series of visual haikus in the spirit of 19th century Japanese poet and wanderer Issa. Through a distillation of impressions, the haiku poets of Issa’s time sought to express moments in a crystallized state. In order to capture experience as a unity and totality, the haiku structure consisted of two elements: the first represented the object, condition, or situation; the second represented perception. The desired result was a nexus of self and world.
Keywords: Avant-Garde; Experimental Film; Video Art; Dada